Supporting the modernization of agricultural advisory system and climate information transfer in Senegal: Case of digitization in two national institutions - Yessoufou, Adjani Nourou-Dine; Worou, Nadine; Dhulipala, Ram; Diouf, Fatimata Bintou; Sene, Atoumane; Sow, Thiwdé Abou; Tall, Thierno Aliou; Gueye, El hadji; Whitbread, Anthony M. (2023)
The report presents the results of a case study on the modernization of the agricultural advisory and climate information transfer system in Senegal, carried out as part of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. Digitalization efforts have focused on the national institutions ANCAR and ANACIM, with the creation of two digital platforms, SAIDA and GTP. The AICCRA-GTP application aims to collect data on various agricultural and climatic aspects, while the ANCAR App facilitates the collection of information for ANCAR's advisory support system. The results show significant advances in process efficiency, data collection and the dissemination of climate information. Although still in their outset, these applications promise significant developments and results for their respective users. The analysis of SAIDA platform usage reveals that among contacted individuals, 57% engaged in a full discussion, with 16% reaching voicemail, 9.7% unanswered rings, and 17.4% non-functional numbers. Extrapolating data, an estimated 7,147 individuals used SAIDA, predominantly men (85%), aged 35 or older (83%), and concentrated in the peanut basin and oriental Senegal. Despite widespread installation, recent use is limited, indicating potential waning interest. Nevertheless, 46% consider SAIDA highly effective, with 84% willing to recommend it.